Cell Block Method: An Imperative Tool for Cytological Diagnosis of Oral Potentially Malignant Lesions - Maham Javed; Rabia Anjum; Gulraiz Zulifqar; Nadia Naseem (ziauddin University, 2024)
Globally, oral squamous cell carcinoma (OSCC) is one of the commonest reported malignancies usually arising from oral potentially malignant lesions (OPMLs) such as leukoplakia, erythroplakia, oral submucous fibrosis (OSMF) and oral lichen planus (OLP). Hence timely and early diagnosis of these disorders is of prime importance to halt their malignant transformation. A search of published works was done using the online databases of PubMed, Scopus, Web of Science, and Cochrane Library". Data from resource-constrained laboratory settings worldwide shows limited documentation of the efficacy of advanced cytological techniques, including LBC and cell block preparations. The oral mucosa can be a suitable area for regular cytological screening due to its easy accessibility. Liquid-based cytology (LBC) can preserve the cellular details and reduce the overlapping of cells, enabling precise interpretation, reducing false-negative results and aiding in the diagnosis of premalignant and malignant lesions of the oral cavity with more accuracy compared to exfoliative cytology.  The remaining sample in LBC can be used in cell block formation and various ancillary tests like immunocytochemistry, immunofluorescence, and molecular studies. Literature showed a scarcity of data available regarding Pakistan. Therefore, the review is aimed to explore the cell block method as a minimally invasive technique for reducing morbidity and mortality associated with OSCC. Keywords: Cell Biology; Oral Squamous Cell Carcinoma; Malignancy.